2018
DOI: 10.1371/journal.pone.0202356
|View full text |Cite
|
Sign up to set email alerts
|

Tissue engineering the human auricle by auricular chondrocyte-mesenchymal stem cell co-implantation

Abstract: Children suffering from microtia have few options for auricular reconstruction. Tissue engineering approaches attempt to replicate the complex anatomy and structure of the ear with autologous cartilage but have been limited by access to clinically accessible cell sources. Here we present a full-scale, patient-based human ear generated by implantation of human auricular chondrocytes and human mesenchymal stem cells in a 1:1 ratio. Additional disc construct surrogates were generated with 1:0, 1:1, and 0:1 combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 53 publications
(112 reference statements)
2
67
0
Order By: Relevance
“…Heatmap representing the proportion of publications by year that utilized specific translational research methodologies from construct characterization to human trial to investigate otologic tissue engineering 15,25‐35,38‐43,45,46,107‐144 …”
Section: Discussionmentioning
confidence: 99%
“…Heatmap representing the proportion of publications by year that utilized specific translational research methodologies from construct characterization to human trial to investigate otologic tissue engineering 15,25‐35,38‐43,45,46,107‐144 …”
Section: Discussionmentioning
confidence: 99%
“…Cohen et al demonstrated the successful outcome of patient-specific human ear cartilage engineered exclusively with human cell sources without extensive in vitro cell expansion prior to implantation. This study was a critical step towards the clinical application of tissue engineering for ear cartilage reconstruction [27].…”
Section: Discussionmentioning
confidence: 99%
“…Several trials showed that a mixture of auricular chondrocytes and MSCs yielded cartilage that was equivalent to constructs made from solely chondrocytes. The ratio of chondrocytes and MSCs varied from 1:1 to 1:3 [76,77] . A recent clinical trial of microtia reconstruction with tissueengineered cartilage was published in 2018 [78].…”
Section: Auricular Cartilage Tissue Engineeringmentioning
confidence: 99%
“…The reconstructed external ear maintained its shape up to 2 years. The progress of human auricular cartilage tissue engineering is summarized in Table 4 [70][71][72][73][74][75][76][77][78][79].…”
Section: Auricular Cartilage Tissue Engineeringmentioning
confidence: 99%